Pengembangan Buku Interaktif untuk Meningkatkan Kemampuan Emosional Anak Usia Dini di LPA Sunshine UNESA: Development of Interactive Books to Improve the Emotional Abilities of Early Childhood at LPA Sunshine UNESA - Rahmawati, Febriani; Nurhenti Dorlina Simatupang; Widayati, Sri (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
The development of early childhood abilities includes physical, social, emotional and cognitive development. This research was designed to develop interactive books for the emotional abilities of early childhood at LPA Sunshine Unesa. This research uses the RnD method with the ADDIE stages. The results of the research show that the Wilcoxon test that has been carried out, namely the Wilcoxon Test Statistics Test, Asymp.sig (2-Tailed) shows a value of 0.005, so it is based on the basis for decision making, namely if the significance value is <0.05 then Ha is accepted and Ho is rejected. Apart from that, it is supported by the Wilcoxon test of ranks, namely that the negative ranks of 10 children did not experience a decrease in either the mean ranks or the sum of ranks. Then the positive ranks have an increase reaching 5.50 in the mean ranks and the sum of ranks is 55. The conclusion from this ranks table is that from the results of the pre-test and post-test there has been an increase, namely in the mean ranks, namely 5.50 and the sum of ranks is 55. The conclusion of this research is that the development of interactive books can improve the emotions of young children at LPA Sunshine Unesa.   ABSTRAK  Pengembangan kemampuan anak usia dini mencakup perkembangan fisik, sosial, emosi, dan kognitif. Penelitian ini disusun untuk mengembangkan buku interaktif untuk kemampuan emosional anak usia dini di LPA Sunshine Unesa. Penelitian ini menggunakan metode RnD dengan tahapan ADDIE. Hasil penelitian menunjukkan uji Wilcoxon yang telah dilakukan yaitu Test Statistics Uji Wilcoxon, Asymp.sig (2-Tailed) menunjukkan nilai 0,005 maka berdasarkan dasar pengambilan keputusan yaitu apabila nilai signifikansi < 0,05 maka Ha diterima dan Ho ditolak. Selain itu didukung oleh uji wilcoxon dari ranks yaitu negative ranks dari 10 anak tidak ada yang mengalami penurunan baik dari mean ranks atau sum of ranks. Kemudian positive ranks nya terdapat kenaikan mencapai 5.50 pada mean ranks dan sum of ranks nya 55. Kesimpulan dari tabel ranks ini adalah dari hasil pre-test dan post-test  nya mengalami kenaikan yaitu pada mean ranks yaitu 5.50 dan sum of ranks nya adalah 55. Kesimpulan pada penelitian ini yaitu pengembangan buku interaktif mampu meningkatkan emosional anak usia dini di LPA Sunshine Unesa.